Метод измерения показателей качества и энергопотребления в электрических сетях - Гриб, Олег Герасимович; Жданов, Р. В.; Гапон, Дмитрий Анатольевич; Зуев, Андрей Александрович (Донецкий национальный технический университет, 2013)
Описан метод измерения параметров электрических сигналов промышленной сети, использующий аппроксимацию входного сигнала функцией специального вида с помощью метода наименьших квадратов. Приведены основные формулы и соотношения. Показаны результаты работы метода на выборочных тестовых сигналах.

The most common methods, used in power solutions are discrete Fourier transform, calculation of RMS values, adaptive filters, wavelet transform, Stockwell-transform. A major shortcoming of existing methods is that they can not properly take into account the various input distortions. This may affect accuracy and efficiency of the device whiles the various transient events. The measurement method of power signals based on least square approximation is described in this paper. Curve fit function includes high harmonics, frequency, it’s rate of change and linear components. Goals of method are good flexibility and performance. Measuring time can be chosen between half to ten periods of nominal frequency with no penalty while interval is not integer number of periods. Also, this method allows to assess the quality of approximation as the standard deviation of the curve fit of the original signal, referred to the amplitude of the fundamental harmonic. Application of quality assessment approximations can significantly enhance the sustainability of the measuring elements to all kinds of disturbances caused by transients in the system. On other hand, method demands powerful hardware for real time calculation. Simulation results on highly corrupted current signal are given. Simulation results confirm the high efficiency and stability of the method. For estimating amplitude of the harmonics enough two to three periods of the fundamental harmonic, while high accuracy measurements of frequency demands more than five periods. Described method can be successfully used in many applications that require measurement of the considered parameters of the electric signal.
Power Quality and Consumption Estimation Method
Keywords: электроэнергия; метод наименьших квадратов; потребители; сигнал электрический; аппроксимация; power system; power quality; least squares method